An exceptionally flexible hydrogen-bonded organic framework with large-scale void regulation and adaptive guest accommodation abilities - Huang, Qiuyi; Li, Wenlang; Mao, Zhu; Qu, Lunjun; Li, Yang; Zhang, Hao; Yu, Tao; Yang, Zhiyong; Zhao, Juan; Zhang, Yi; Aldred, Matthew P.; Chi, Zhenguo (Nature communications, 2019)
Flexible hydrogen-bonded organic frameworks (FHOFs) are quite rare but promising for applications in separation, sensing and host-guest chemistry. They are difficult to stabilize, making their constructions a major challenge. Here, a flexible HOF (named 8PN) with permanent porosity has been successfully constructed. Nine single crystals of 8PN with different pore structures are obtained, achieving a large-scale void regulation from 4.4% to 33.2% of total cell volume. In response to external stimuli, multimode reversible structural transformations of 8PN accompanied by changes in luminescence properties have been realized. Furthermore, a series of high-quality co-crystals containing guests of varying shapes, sizes, aggregation states and even amounts are obtained, showing that 8PN can adapt to different guests by regulating the molecular conformations and assembling forms of its building blocks. The unexpected flexibility of 8PN makes it a promising material for enriching the applications of existing porous materials. Flexible hydrogen-bonded organic frameworks (FHOFs) are challenging in fabrication but promising materials for applications in separation and sensing. Here, the authors report a stimuli responsive and flexible HOF which can adapt to different guests by regulating the molecular conformation.